Ability of pulse oximetry-derived indices to predict hypotension after spinal anesthesia for cesarean delivery: A systematic review and meta-analysis. - Yuriko Kondo; Eishin Nakamura; Hisashi Noma; Sayuri Shimizu; Takahisa Goto; Takahiro Mihara (PLoS ONE)
Cesarean deliveries are often performed under spinal anesthesia because of the reduced risk of complications compared with that of general anesthesia. However, hypotension frequently occurs and adversely affects both the mother and fetus. Indices, such as the perfusion index (PI) and pleth variability index (PVI), which are derived from pulse oximetry have been used in numerous studies to predict hypotension after spinal anesthesia. However, their predictive abilities remain controversial. This study aimed to investigate the ability of PI and PVI, measured before the initiation of spinal anesthesia, to predict hypotension after spinal anesthesia in patients undergoing cesarean deliveries. To this end, we conducted a systematic review and meta-analysis. We searched MEDLINE, Embase, Web of Science, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, ClinicalTrials.gov, European Union Clinical Trials Register, World Health Organization International Clinical Trials Registry Platform, and University Hospital Medical Information Network Clinical Trials Registry databases from inception until June 15, 2023. We included retrospective and prospective observational studies and randomized controlled trials that assessed the ability of PI and PVI, measured before the initiation of spinal anesthesia, to predict hypotension after spinal anesthesia during cesarean delivery. We did not restrict our search to specific languages. Of the 19 studies, involving 1437 patients, 17 assessed the PI in 1,311 patients, and 5 assessed the PVI in 344 patients. The summary sensitivity and specificity of the PI were 0.75 (95% confidence interval [CI]: 0.69-0.80) and 0.64 (95%CI: 0.48-0.77), respectively, while those of the PVI were 0.63 (95%CI: 0.47-0.76) and 0.76 (95%CI: 0.64-0.84), respectively. The area under the summary receiver operating characteristic curve was approximately 0.75 for both indexes. Baseline PI and PVI have a moderate predictive ability for hypotension after spinal anesthesia in patients undergoing cesarean delivery.